The Relationship Between Satisfaction with Complaint Handling and Repurchase Intentions: Detecting Moderating Influences in E-Tail - Mateus Nagel; Cristiane Pizzutti dos Santos (BBR: Brazilian Business Review)
This paper examines which factors affect the relationship between consumers’ satisfaction with complaint handling and repurchase intentions. We present a conceptual framework that explains why satisfaction with complaint handling (SATCOM) does not necessary lead to repurchase intention (RI) for online shoppers. The authors test five moderating variables of the relationship between SATCOM and RI: relationship quality (relational factor), economic value, alternative attractiveness (marketplace factor), inferred motives and stability of the failure (failure-related factors). To test our hypotheses, we conducted an online survey with e-shoppers and used moderated regression analysis and a bootstrapping procedure. The findings show that all moderators help to explain the nonlinearity between SATCOM and RI. Hence, this study makes theoretical and managerial contributions related to failures in shopping experiences and repurchase intentions in e-tail.